PERANCANGAN DAN IMPLEMENTASI APLIKASI EDUKASI MENTAL HEALTH MENGGUNAKAN METODE DESIGN THINKING - Munchamimnna; Nuzulul; Krismawati, Era (MSJ : Majority Science Journal, 2023)
This research aims to design and implement User Experience (UX) and User Interface (UI) in a Mental Health education application using the Design Thinking method. Mental health has become an increasingly important issue in society today, requiring efforts to provide effective education in this area. The Design Thinking method is used as the main approach in the application design process, involving four phases: understanding (empathize), observation (observe), ideation (ideate), and prototyping (prototype). Throughout the development process, active participation from various stakeholders is involved, including mental health experts, potential users, and the application development team. The application offers an intuitive and engaging interface, with a focus on adequate user experience and visually appealing design. Various features have been implemented, including splash screens, onboarding, login, home screens, mindfulness, classes, notifications, profiles, order history, and lists. Users can easily access educational materials on mental health, participate in interactive classes, and receive relevant notifications to reinforce their attention to mental health. Through this application, it is expected to increase awareness and understanding of the importance of mental health among the public. By combining good UX and UI principles with the Design Thinking approach, this educational application has the potential to provide an optimal user experience and enhance user engagement in mental health education.